Simplified detection of polyhistidine-tagged proteins in gels and membranes using a UV-excitable dye and a multiple chelator head pair - Raducanu, Vlad-Stefan; Isaioglou, Ioannis; Raducanu, Daniela-Violeta; Merzaban, Jasmeen S.; Hamdan, Samir M. (The Journal of biological chemistry, 2020)
The polyhistidine tag (His-tag) is one of the most popular protein tags used in the life sciences. Traditionally, the detection of His-tagged proteins relies on immunoblotting with anti-His antibodies. This approach is laborious for certain applications, such as protein purification, where time and simplicity are critical. The His-tag can also be directly detected by metal ion–loaded nickel-nitrilotriacetic acid–based chelator heads conjugated to fluorophores, which is a convenient alternative method to immunoblotting. Typically, such chelator heads are conjugated to either green or red fluorophores, the detection of which requires specialized excitation sources and detection systems. Here, we demonstrate that post-run staining is ideal for His-tag detection by metal ion–loaded and fluorescently labeled chelator heads in PAGE and blot membranes. Additionally, by comparing the performances of different chelator heads, we show how differences in microscopic affinity constants translate to macroscopic differences in the detection limits in environments with limited diffusion, such as PAGE. On the basis of these results, we devise a simple approach, called UVHis-PAGE, that uses metal ion–loaded and fluorescently labeled chelator heads to detect His-tagged proteins in PAGE and blot membranes. Our method uses a UV transilluminator as an excitation source, and the results can be visually inspected by the naked eye.